Simulation of the Antenna Azimuth Position Control System with Fuzzy PID-like Controller - Mnushka, O. (My University, 2014)
The paper deals with antenna azimuth control system, which controlled by using conventional proportional-integral-derivate (PID) controllers and both Mamdani-type and Takagi-Sugeno-type fuzzy logic controllers (FLC). In order to obtain system response to various external perturbations the simulation model was developed in Matlab / Simulink environment. System responses with FLC and PID-controller for four various external perturbations are compared.
Keywords: Fuzzy logic; Robust control; Perturbations; simulation; PID